Respon Pertumbuhan Miselium Jamur Tiram Kuning (Pleurotus citrinopileatus) Terhadap Berbagai Formulasi Media Baglog - Thomas Yoga Prasetya Susilo; Ruth Meike Jayanti (Jurnal Pertanian Terpadu, 2026)
Yellow oyster mushroom (Pleurotus citrinopileatus) is one of the edible mushroom commodities that has the potential to be developed as an alternative source of nutritious food. Optimization of the growing media is an important factor in supporting mycelial growth because the substrate must provide lignocellulosic compounds as the main carbon source. This study aimed to analyze the response of mycelial growth rate of yellow oyster mushroom to different baglog media formulations and to determine the best growing media for yellow oyster mushroom spawn development. The research was conducted from June to December 2025 using a randomized block design (RBD) with a single factor, namely media formulation consisting of seven treatments with three replications. The media treatments consisted of combinations of sengon sawdust, cocopeat, corn, and millet. The observed parameter was mycelial growth rate measured on days 7, 14, 21, and 30. Data were analyzed using ANOVA at a 5% significance level followed by Tukey’s test (HSD). The results showed that media formulation had a highly significant effect on mycelial growth rate. Treatment P1 (100% sengon sawdust) produced the highest mycelial growth rate of 0.526 cm/day and was significantly different from other treatments, while treatments P2–P7 produced growth rates ranging from 0.252–0.341 cm/day. Pure sengon sawdust media resulted in faster mycelial growth and earlier baglog colonization due to its high lignocellulose content and porous substrate structure, which supports aeration and optimal mycelial growth.